Protective and Risk Factors for Medical and Nursing Staff Suffering From Psychological Symptoms During COVID-19 - Luo, Hailong; Yao, Huiqi; Xi, Yuandi; Zhang, Zhun; Li, Jia; Li, Jie; Wang, Xuewen; Zhong, Zhixiong; Lv, Yan (Frontiers in Psychology, 2021)
Background: At the very beginning of the epidemic of coronavirus disease 2019(COVID-19) in China, not only the public but also the medical staff were confronting with psychological challenging and suffering for the highly infectious and unknown characteristics of the disease. In this study, we surveyed the psychological symptoms like anxiety, depression, and sleep disorder for medical staff. Method: A questionnaire star/ WeChat link-based survey of GAD-7 (Generalized Anxiety Disorder, GAD-7), PHQ-9(Patient Health Questionnaire-9) depression, ISI (Insomnia Severity Index) scales, SSS(Social Support Scales) besides lifestyle, and income level were conducted and checked for 8288 medical staff from almost 24 provinces in China. Pearson Chi-square and Mann-Whitney U test was used for the evaluation of single risk factors and significant differences in psychological symptoms before and during the defense. Biliary Logistic regression analyses were conducted for the risk factors of anxiety, depression, and sleep disorder symptoms. Result: The medical staff had a high incidence of psychological symptoms, which was more prominent during the COVID-19 defense. Comparatively, females, nurses, first-line healthcare, never sports, low income were risk factors for psychological symptoms; meanwhile, social support including objective support, subjective support, and support utility and regular sports over 3 times per week were protective and manageable elements for psychological symptoms of medical staff. Conclusion: The susceptibility of psychological symptoms of medical staff should raise the long-term attention of policymakers and the public, the current worsening of the mental health problem of medical staff could be eased by providing adequate social support during the CIVOD-19 defence and afterward.